Funding for radiation research: past, present and future. (3rd July 2019) - Cho, Kunwoo; Imaoka, Tatsuhiko; Klokov, Dmitry; Paunesku, Tatjana; Salomaa, Sisko; Birschwilks, Mandy; Bouffler, Simon; Brooks, Antone L.; Hei, Tom K.; Iwasaki, Toshiyasu; Ono, Tetsuya; Sakai, Kazuo; et al.
Abstract: For more than a century, ionizing radiation has been indispensable mainly in medicine and industry. Radiation research is a multidisciplinary field that investigates radiation effects. Radiation research was very active in the mid- to late 20th century, but has then faced challenges, during which time funding has fluctuated widely. Here we review historical changes in funding situations in the field of radiation research, particularly in Canada, European Union countries, Japan, South Korea, and the US. We also provide a brief overview of the current situations in education and training in this field. A better understanding of the biological consequences of radiation exposure is becoming more important with increasing public concerns on radiation risks and other radiation literacy. Continued funding for radiation research is needed, and education and training in this field are also important.